Civic Culture In "Nganggung Dulang" Tradition To Strengthen Local Wisdom Values - Ahmad Ridwan; Suharno Suharno; Sindy Sataroh (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
This paper stems from the low awareness of the community regarding efforts to preserve a local tradition. The study aims to (1) describe the values of local wisdom found in the Nganggung Dulang tradition, (2) explore the community's understanding of civic culture within the Nganggung Dulang tradition, (3) identify the implementation of civic culture within the Nganggung Dulang tradition, and (4) analyze the roles of the government and the community in maintaining the existence of the Nganggung Dulang tradition. This research employs a qualitative approach using ethnographic methods. Subject determination uses purposive techniques. Data collection involves observation, interviews, and documentation. Data analysis applies the interactive model of Miles, Huberman, and Saldana, involving data condensation, data display, and conclusion drawing. The research findings indicate (1) the values of local wisdom in the Nganggung Dulang tradition include religious values, mutual cooperation, social care, and kinship values, (2) the community's understanding of civic culture in the Nganggung Dulang tradition strengthens local wisdom with good values, evidenced by the community's awareness of the historical background, purpose, and process of the Nganggung Dulang tradition, (3) the implementation of civic culture in the Nganggung Dulang tradition occurs during events such as funerals, Isra Mikraj of Prophet Muhammad SAW, Ruwah Bulan Syaban, Eid al-Fitr, Eid al-Adha, Islamic New Year, and Maulid of Prophet Muhammad SAW, and (4) the government and community of Ranggas Village, Bangka Belitung Islands Province, play significant roles in preserving the Nganggung Dulang tradition.